Stranger from abroad : Hannah Arendt, Martin Heidegger, friendship and forgiveness - Maier-Katkin, Daniel, 1945- 1945- (W.W. Norton & Company, 2010)
Shaking up the content and method by which generations of students had studied Western philosophy, Martin Heidegger sought to ennoble Man's existence in relation to Death. Yet in a time of crisis, he sought personal advancement, becoming the most prominent German intellectual to join the Nazis. Hannah Arendt, his brilliant, beautiful student and young Jewish lover, sought to enable a decent society of human beings in relation to one other. She was courageous in the time of crisis. Years later, she was even able to forgive Heidegger and to find in his behavior an insight into Nazism that would influence her reflections on "the banality of evil"--a concept that remains bitterly controversial and profoundly influential to this day. This book dramatizes some of the greatest questions of the twentieth century--revealing bonds connecting the personal, philosophical, and political, highlighting the responsibility of intellectuals in dark times.--From publisher description.